Psychological Factors and Reference Potential of Market Mavens - Puspa, Jofi (Gadjah Mada International Journal of Business, 2009)
The function of a market maven in the information transfer processes is apparently related to oneâs psychological states such as inherent knowledge and involvement level. Understanding reference potential of mavens seems to be relevant to comprehend the implicit value of a maven in the communication process. This study shows that (1) apparently, maven groups can be clearly distinguished from a non-maven group on the basis on inherent personal knowledge level and involvement level; (2) market mavens have a high reference potential which confirmed their function in WOM-information.